Вкус рая: роман / Конни Мейсон - Мейсон Конни (Грешные желания, 2007)
Экземпляры: аб. ЦБ (2016.12.13) / Инвентарный номер: 2656 / Цена: / Сис.шифр: 84(7Сое) / Авт.знак: М45 / ГРНТИ: 17 / ББК: 84(7 Сое)